Fundamental of constant electrode melting rate control for electroslag fusion welding - Haoran Xu; Baokuan Li; Xuechi Huang; Yu Wang; Yanchun Lou; Zhongqiu Liu (Journal of Materials Research and Technology)
In order to solve the problem of horizontal depth of fusion fluctuation during electroslag fusion welding (ESFW) as well as to improve the uniformity of the distribution of grain size, solute elements and non-metallic inclusions, the present study establishes a fundamental theory of constant electrode melting rate control of ESFW based on basic principles of heat transfer, proposes for the first time a mechanism for regulating the voltage and slag, and develops an experimentally validated transient 2D multiphysics field coupling model (2.2 % error in molten pool width). Key findings show the electrode melting rate, influenced by slag temperature, electrode geometry, and immersion depth, increases from 4.04 kg/min (0 mm immersion, intermittent clicking slag pool) to 42.4 kg/min (15 mm immersion). Both regulation mechanisms can maintain the stability of slag pool temperature throughout the entire process. Slag regulation mechanism stabilizes slag pool depth (18.93 % reduction during stabilization) but reduces horizontal melting depth (10.42 % decrease at 42.4 kg/min). As ESFW proceeds, the trapezoidal slag pool generates downward molten metal flow and bidirectional vortices (10−3 m/s for molten pool and stronger convection in slag pool), which is exacerbated by accelerated droplet formation (0.3 m/s) at higher melting rate. Lower melting rates (4.04–8.07 kg/min) reduce molten pool depth growth (89.66 % increase), improving solidification quality, whereas high rates (42.4 kg/min) enhance depth (223.81 % increase) and energy efficiency. The electrical parameters obtained in this study can be proportionally applied to electroslag fusion welded components of other geometric dimensions.